Case report: Combined cervical incision with an intercostal uniportal video-assisted thoracoscopic surgery approach for mediastinal brachial plexus schwannoma - Wang, Linlin; Ge, Lihui; Ren, Yi (Frontiers in Oncology, 2023)
Mediastinal neurogenic tumors primarily originate from the intercostal and sympathetic nerves, whereas schwannomas originating from the brachial plexus are rare. Surgical intervention for such tumors is complex and associated with the risk of postoperative upper limb dysfunction due to their unique anatomical location. In this report, we present the case of a 21-year-old female diagnosed with a mediastinal schwannoma, who underwent a novel surgical approach combining cervical incision and intercostal uniportal video-assisted thoracoscopic surgery (VATS). Our study reviewed the patient's clinical presentation, treatment approach, pathology, and prognosis. The findings of this study demonstrate that the cervical approach, combined with intercostal uniportal VATS, is a feasible surgical method for the removal of mediastinal schwannomas originating from the brachial plexus.